2021
DOI: 10.2217/fon-2021-0597
|View full text |Cite
|
Sign up to set email alerts
|

Immunogenicity and Safety of the Coronavac Vaccine in Patients with Cancer Receiving Active Systemic Therapy

Abstract: Aim: To evaluate the immunogenicity and safety of the CoronaVac vaccine in patients with cancer receiving active systemic therapy. Methods: This multicenter, prospective, observational study was conducted with 47 patients receiving active systemic therapy for cancer. CoronaVac was administered as two doses (3 μg/day) on days 0 and 28. Antibody level higher than 1 IU/ml was defined as ‘immunogenicity.’ Results: The immunogenicity rate was 63.8% (30/47) in the entire patient group, 59.5% (25/42) in those receivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
36
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(40 citation statements)
references
References 19 publications
2
36
0
2
Order By: Relevance
“…Growing evidence suggests that among cancer patients, those with hematologic malignancies are less likely to develop robust anti-S IgG after SARS-CoV-2 vaccination due to immunosuppression induced by disease-related lineage defects and its treatments. [ 3 , 17 , 35 , 36 ] Consistently, when stratifying by type of cancer, we observed that patients with hematological malignancies had the highest risk of being non-responders after complete COVID-19 vaccination. Furthermore, oncologic regimens based on monoclonal antibodies (anti-CD20, anti-CD38), Bruton tyrosine kinase-, Bcl-2-, Janus Kinase 1/2- inhibitors, and chimeric antigen receptor T-cell therapy have been associated with lower seroconversion rates.…”
Section: Discussionsupporting
confidence: 70%
See 3 more Smart Citations
“…Growing evidence suggests that among cancer patients, those with hematologic malignancies are less likely to develop robust anti-S IgG after SARS-CoV-2 vaccination due to immunosuppression induced by disease-related lineage defects and its treatments. [ 3 , 17 , 35 , 36 ] Consistently, when stratifying by type of cancer, we observed that patients with hematological malignancies had the highest risk of being non-responders after complete COVID-19 vaccination. Furthermore, oncologic regimens based on monoclonal antibodies (anti-CD20, anti-CD38), Bruton tyrosine kinase-, Bcl-2-, Janus Kinase 1/2- inhibitors, and chimeric antigen receptor T-cell therapy have been associated with lower seroconversion rates.…”
Section: Discussionsupporting
confidence: 70%
“…Following title and abstract review, 1,233 records were excluded given that they reported non-original findings, did not include cancer patients, or did not assess COVID-19 vaccines’ immunogenicity. Of the 54 articles that underwent full-text review, 35 articles[ [17] , [18] , [19] , [20] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] ] were considered eligible and were included in the meta-analysis ( Figure 1 ).
Figure 1 The PRISMA flowchart summarizing the process for the identification of eligible studies.
…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The vast majority of included studies evaluated vaccines developed by Pfizer (BNT162b2) or Moderna (mRNA-1273). Thirteen studies included patients who received the vaccine developed by Janssen (Ad26.COV2.S) [ [25] , [26] , [27] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] ], nine included patients vaccinated with the AstraZeneca vaccine (ChAdOx1) [ [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] ], three included patients receiving the CoronaVac vaccine (Sinovac Biotech) [ [50] , [51] , [52] ], and one randomized controlled trial evaluated the vaccine developed by Novavax (NVX-CoV2373) vaccine [ 53 ]. One study included patients receiving the BBV152-Covaxin (Bharat Biotech) vaccine [ 44 ] and one included patients receiving the BBIBP-CorV (Sinopharm) vaccine [ 54 ].…”
Section: Resultsmentioning
confidence: 99%